Snow grain size retrieval over the polar ice sheets with the Ice, Cloud, and land Elevation Satellite (ICESat) observations. (February 2017) - Yang, Yuekui; Marshak, Alexander; Han, Mei; Palm, Stephen P.; Harding, David J.
Abstract: Snow grain size is an important parameter for cryosphere studies. As a proof of concept, this paper presents an approach to retrieve this parameter over Greenland, East and West Antarctica ice sheets from surface reflectances observed with the Geoscience Laser Altimeter System (GLAS) onboard the Ice, Cloud, and land Elevation Satellite (ICESat) at 1064 nm. Spaceborne lidar observations overcome many of the disadvantages in passive remote sensing, including difficulties in cloud screening and low sun angle limitations and hence tend to provide more accurate and stable retrievals. Results from the GLAS L2A campaign, which began on 25 September and lasted until 19 November, 2003, show that the mode of the grain size distribution over Greenland is the largest (~300 µm) among the three, West Antarctica is the second (~220 µm) and East Antarctica is the smallest (~190 µm). Snow grain sizes are larger over the coastal regions compared to inland the ice sheets. These results are consistent with previous studies. Applying the broadband snow surface albedo parameterization scheme developed by Garder and Sharp (2010) to the retrieved snow grain size, ice sheet surface albedo is also derived. In the future, more accurate retrievals can be achieved with multiple wavelengths lidar observations. Highlights: ICESat surface reflectance observations at 1064 nm is sensitive to snow grain size. Spaceborn lidars have advantages over passive techniques for grain size retrieval. Grain sizes are retrieved over Greenland and Antarctica for the ICES at L2A campaign.